Giusepe Tommasi Lampedusa: History and time in Il Gattopardo - Clara Corona (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The personality of Giuseppe Tomasi di Lampedusa, as well as his work, escape a conventional cataloging. Heir to an ancient Sicilian aristocratic family, married to the Latvian psychoanalyst Licy Wolff at his descendant of an important Baltic family, distinguished connoisseur of English and French literature, the writer is actually an outsider in the social and cultural landscape of Italy war rather "European" that "Italian" and certainly "Sicilian." Author of one novel, The Leopard, whose premises and whose echoes and intertextual references are also tracking down the handful of stories and especially in La Sirena and in autobiographical memory, just other titles of his limited body of literature, and in this sense in fact the author of one book significantly written in the point of death, Lampedusa reworks the story of a Sicilian aristocratic family in the twenty years 1860-80, against the background of the Italian Risorgimento, his family experiences electing Sicily Don Fabrizio Salina universal metaphor the fragile and ephemeral human story that crosses the historical time. The ironic and at the same time tragic spirit of Lampedusa-Salina, the feeling of death and the intimate disenchantment with the "magnificent and progressive" fortunes in the history of man, Giuseppe Tomasi reconnects to the highest Sicilian literary line